2022
DOI: 10.18844/cjes.v17i1.6700
|View full text |Cite
|
Sign up to set email alerts
|

Developing the social activities of primary school students with hearing impairment using technologies

Abstract: It is known that the use of technology to support individualization and motivation in education programs for hearing-impaired individuals has positive results. This research aims to reveal the views of teachers, students, and parents to develop the social activities of hearing-impaired students by supporting them with technology. This research was conducted with the phenomenology pattern, one of the qualitative research designs. Data were collected through semi-structured interview forms prepared separately fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many studies shed light on the importance of technology regarding the social inclusion of adolescents with hearing impairment. Ussenova et al (2022) conducted a study on developing social activities of SWHI using technology. They explored the problems faced by students SWHI in social activities and examined the effect of technology in lessening those problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies shed light on the importance of technology regarding the social inclusion of adolescents with hearing impairment. Ussenova et al (2022) conducted a study on developing social activities of SWHI using technology. They explored the problems faced by students SWHI in social activities and examined the effect of technology in lessening those problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, hearing impaired athletes may have some psychological disadvantages even if they do not have a physical deficiency compared to non-hearing impaired athletes. Studies have revealed that hearing impairment can lead to communication difficulties, rejection by peers, introversion, adjustment problems and feeling neglected (Ussenova et al, 2022). Hearing impairment limits the ability of hearing impaired people to communicate with their environment.…”
Section: Introductionmentioning
confidence: 99%
“…Children under the age of 15 comprise 34 million of these people. According to the prediction of World Health Organization, 2,5 billion people will have different levels of hearing by 2050 [1]. According to the World Health Organization (WHO), 60% of all cases of the loss of hearing ability in developing countries are related to the lack of preventive measures [2].…”
Section: Introductionmentioning
confidence: 99%